2002
DOI: 10.1159/000052000
|View full text |Cite
|
Sign up to set email alerts
|

Total Gastrectomy Is Not Always Necessary for Advanced Gastric Cancer of the Cardia

Abstract: Background: It is unclear whether total gastrectomy (TG) is always necessary for gastric cancer of the cardia. We therefore investigated whether cardiac cancers treated by TG would have been cured by proximal gastrectomy (PG). Methods: Photocopies of the resected stomachs of 55 patients who had received TG for cardiac cancer were reviewed. A simulated resection line for PG was drawn connecting a point 5 cm from the pyloric ring on the lesser curvature with a point 15 cm from the pyloric ring on the greater cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Early gastric cancer usually does not present metastasis to lymph node stations 5, 6, 4d or 12, which are not completely dissected during proximal gastrectomy. Survival outcomes after proximal gastrectomy have been reported to be similar with those after total gastrectomy [14,15,16,17]. Our results also showed that only lymph node stations 2, 3 and 7 were the sites where lymph node metastasis occurs from early gastric cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Early gastric cancer usually does not present metastasis to lymph node stations 5, 6, 4d or 12, which are not completely dissected during proximal gastrectomy. Survival outcomes after proximal gastrectomy have been reported to be similar with those after total gastrectomy [14,15,16,17]. Our results also showed that only lymph node stations 2, 3 and 7 were the sites where lymph node metastasis occurs from early gastric cancer.…”
Section: Discussionsupporting
confidence: 84%
“…The IEBLDs of the remaining stations were lower than that of station 1, 2, 3, 7, 9, and 11p, and was zero in stations 4sa, 4d, 6, 8a, 10, and 11d; thus, lymph node dissection of some of these stations could be omitted. If we omit the supra-and infrapyloric lymph nodes, then the distal part of the stomach might be preserved [17]. In addition, the spleen could be preserved if the station 10 lymph node dissection was omitted, even in cases with advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although the numerical LN staging system has been reported to be superior to the topographic LN system in regard to estimating prognosis, the latter has its own importance in defining the extent of LN dissection17, 18. Patterns of LN metastasis are particularly important in designing limited surgery, such as pylorus‐preserving gastrectomy or proximal gastrectomy15, 19, 20, especially in countries such as Japan and Korea where the incidence of early gastric cancer is high.…”
Section: Discussionmentioning
confidence: 99%